Sliding Up an Elliptical Loop

A massive point-particle is sliding on the inside of a smooth elliptical loop, described by the following equation (distances in meters): x 2 9 + y 2 4 = 1. \frac{x^2}{9} + \frac{y^2}{4} = 1. Initially, the particle is at ( x , y ) = ( 3 , 0 ) (x,y) = (3,0) , and its velocity is upward and tangential to the curve. Gravity is 10 m/s 2 10\text{ m/s}^2 in the y -y direction.

What is the minimum initial speed ( ( in m/s ) \text{m/s}) required for the particle to reach ( x , y ) = ( 0 , 2 ) (x,y) = (0,2) without flying off of the loop on the way there?


The answer is 9.2195.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
Feb 1, 2018

The position, velocity and acceleration vectors of a particle touching the ellipse can be given by r = ( 3 cos θ 2 sin θ ) r ˙ = ( 3 sin θ 2 cos θ ) θ ˙ r ¨ = ( 3 sin θ 2 cos θ ) θ ¨ ( 3 cos θ 2 sin θ ) θ ˙ 2 \mathbf{r} \; = \; \binom{3\cos\theta}{2\sin\theta} \hspace{1cm} \mathbf{\dot{r}} \; = \; \binom{-3\sin\theta}{2\cos\theta}\dot{\theta} \hspace{1cm} \mathbf{\ddot{r}} \; = \; \binom{-3\sin\theta}{2\cos\theta}\ddot{\theta} - \binom{3\cos\theta}{2\sin\theta}\dot{\theta}^2 The normal reaction between the particle and the ellipse will be of the form R = m λ ( 2 cos θ 3 sin θ ) \mathbf{R} \; = \; -m\lambda\binom{2\cos\theta}{3\sin\theta} where λ > 0 \lambda > 0 , and the equation of motion of the particle is m r ¨ = R + ( 0 m g ) ( ) m\mathbf{\ddot{r}} \; = \; \mathbf{R} + \binom{0}{-mg} \hspace{3cm} (\star) Taking the scalar product of ( ) (\star) with ( 3 sin θ 2 cos θ ) \binom{-3\sin\theta}{2\cos\theta} , we obtain ( 9 sin 2 θ + 4 cos 2 θ ) θ ¨ + 5 sin θ cos θ θ ˙ 2 = 2 g cos θ d d θ [ 1 2 ( 9 sin 2 θ + 4 cos 2 θ ) θ ˙ 2 + 2 g sin θ ] = 0 1 2 ( 9 sin 2 θ + 4 cos 2 θ ) θ ˙ 2 + 2 g sin θ = 1 2 v 2 θ ˙ 2 = v 2 4 g sin θ 4 + 5 sin 2 θ \begin{aligned} (9\sin^2\theta + 4\cos^2\theta)\ddot{\theta} + 5\sin\theta\cos\theta \dot{\theta}^2 & = \; -2g\cos\theta \\ \frac{d}{d\theta}\left[\tfrac12(9\sin^2\theta + 4\cos^2\theta)\dot{\theta}^2 + 2g\sin\theta\right] & = \; 0 \\ \tfrac12(9\sin^2\theta + 4\cos^2\theta)\dot{\theta}^2 + 2g\sin\theta & = \; \tfrac12v^2 \\ \dot{\theta}^2 & = \; \frac{v^2 - 4g\sin\theta}{4 + 5\sin^2\theta} \end{aligned} Taking the scalar product of ( ) (\star) with ( 2 cos θ 3 sin θ ) \binom{2\cos\theta}{3\sin\theta} , we obtain that λ = 3 ( 2 θ ˙ 2 g sin θ ) 4 + 5 sin 2 θ = 3 ( 4 + 5 sin 2 θ ) 2 [ 2 v 2 g sin θ ( 12 + 5 sin 2 θ ) ] \lambda \; = \; \frac{3(2\dot{\theta}^2 - g\sin\theta)}{4 + 5\sin^2\theta} \; = \; \frac{3}{(4 + 5\sin^2\theta)^2}\big[ 2v^2 - g\sin\theta(12 + 5\sin^2\theta)\big] and hence, to reach the top of the ellipse, we must have λ 0 \lambda \ge 0 throughout the motion, and so 2 v 2 g sin θ ( 12 + 5 sin 2 θ ) 0 θ 1 2 π 2v^2 \; \ge \; g\sin\theta(12 + 5\sin^2\theta) \hspace{1cm} 0 \le \theta \le \tfrac12\pi The RHS of this inequality is an increasing function of θ \theta , so we want 2 v 2 17 g 2v^2 \ge 17g , and hence v 9.5 g = 9.219544457 m s 1 v \ge \boxed{\sqrt{9.5g} = 9.219544457} \mathrm{m\,s}^{-1} .

Sir, in the last and second last lines, it should be 2 v 2 17 g 2v^2 \geq 17g instead of v 2 v^2 as derived by you in the preceding line.

Harsh Poonia - 2 years, 1 month ago
Harsh Poonia
Aug 30, 2019

x 2 9 + y 2 4 = 1 \dfrac{x^2}{9}+\dfrac{y^2}{4}=1 Taking derivative, 2 x 9 d x + 2 y 4 d y = 0 \text{Taking derivative, }\dfrac{2x}{9}dx+\dfrac{2y}{4}dy=0 d y d x = 4 x 9 y ( ) \dfrac{dy}{dx}=- \dfrac{4x}{9y} \cdots (\star)

At the highest point, for the particle, m g + N by loop = m d v d t . m \textbf{g}+ \textbf{N}_{\text{by loop}} =m \dfrac{d\textbf{v}}{dt}. For the particle to reach the top without losing contact with the loop with minimum initial velocity, at the highest point, the value of N \textbf{N} should be just negligibly greater than 0 0 . So, d v d t = g . \dfrac{d\textbf{v}}{dt}=\textbf{g}. Here's how we can find acceleration at the point ( 0 , 2 ) (0,2) : d V x = v ( cos d θ 1 ) 0 , d V y = v sin d θ v d θ dV_x=v(\cos d\theta -1) \approx 0, dV_y =v \sin d\theta \approx v d \theta So d v d t = v d θ d t = 2 v 2 9 = g . (Since d x / d t = v ) \dfrac{d\textbf{v}}{dt}= v \dfrac{d\theta}{dt} =\dfrac{-2v^2}{9}=-g. \text{ (Since } dx/dt=v) So v 2 = 9 g 2 v 0 2 = 17 g 2 . v^2=\dfrac{9g}{2}\implies \boxed{v_0^2=\dfrac{17g}{2}}.

@Harsh Poonia can we do it without calculus With only work energy theorem

A Former Brilliant Member - 1 year, 9 months ago

Log in to reply

You would need calculus to get the radius of curvature and acceleration.

Harsh Poonia - 1 year, 8 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...